Omics Profiling of S2P Mutant Fibroblasts as a Mean to Unravel the Pathomechanism and Molecular Signatures of X-Linked MBTPS2 Osteogenesis Imperfecta - Lim, Pei Jin; Marfurt, Severin; Lindert, Uschi; Opitz, Lennart; Ndarugendamwo, Timothée; Srikanthan, Pakeerathan; Poms, Martin; Hersberger, Martin; Langhans, Claus-Dieter; Haas, Dorothea; Rohrbach, Marianne; Giunta, Cecilia (Frontiers in Genetics, 2021)
Osteogenesis imperfecta (OI) is an inherited skeletal dysplasia characterized by low bone density, bone fragility and recurrent fractures. The characterization of its heterogeneous genetic basis has allowed the identification of novel players in bone development. In 2016, we described the first X-linked recessive form of OI caused by hemizygous MBTPS2 missense variants resulting in moderate to severe phenotypes. MBTPS2 encodes site-2 protease (S2P), which activates transcription factors involved in bone (OASIS) and cartilage development (BBF2H7), ER stress response (ATF6) and lipid metabolism (SREBP) via regulated intramembrane proteolysis. In times of ER stress or sterol deficiency, the aforementioned transcription factors are sequentially cleaved by site-1 protease (S1P) and S2P. Their N-terminal fragments shuttle to the nucleus to activate gene transcription. Intriguingly, missense mutations at other positions of MBTPS2 cause the dermatological spectrum condition Ichthyosis Follicularis, Atrichia and Photophobia (IFAP) and Keratosis Follicularis Spinulosa Decalvans (KFSD) without clinical overlap with OI despite the proximity of some of the pathogenic variants. To understand how single amino acid substitutions in S2P can lead to non-overlapping phenotypes, we aimed to compare the molecular features of MBTPS2-OI and MBTPS2-IFAP/KFSD, with the ultimate goal to unravel the pathomechanisms underlying MBTPS2-OI. RNA-sequencing-based transcriptome profiling of primary skin fibroblasts from healthy controls, MBTPS2-OI and MBTPS2-IFAP/KFSD patients was performed to identify genes that are differentially expressed in MBTPS2-OI and MBTPS2-IFAP/KFSD individuals compared to controls. We observed that SREBP-dependent genes are more downregulated in OI than in IFAP/KFSD. This is coupled to alterations in the relative abundance of fatty acids in MBTPS2-OI fibroblasts in vitro, while no consistent alterations in the sterol profile were observed. Few OASIS-dependent genes are suppressed in MBTPS2-OI, while BBF2H7- and ATF6-dependent genes are comparable between OI and IFAP/KFSD patients and control fibroblasts. Importantly, we identified genes involved in cartilage physiology that are differentially expressed in MBTPS2-OI but not in MBTPS2-IFAP/KFSD fibroblasts. In conclusion, our data provide clues to how pathogenic MBTPS2 mutations cause skeletal deformities via altered fatty acid metabolism or cartilage development that may affect bone development, mineralization and endochondral ossification.